High-entropy alloy combined SiC hard composite material and preparation method thereof
By combining high-entropy alloys with SiC and using discharge plasma sintering technology, the problems of high sintering difficulty and low toughness of SiC composite materials are solved, and the preparation of high-performance SiC hard composite materials is realized, expanding its application field.
Patent Information
- Application Number
- CN202510037377.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
SiC composites have limited their application areas due to complex phase transition, difficult sintering and low toughness, especially in reducing sintering temperature and improving material toughness.
High-entropy alloys (such as AlMnCuFeTi and AlZnCuFeTi) are combined with SiC, and metal-bonded phase silicon carbide hard composite materials are prepared through discharge plasma sintering (SPS) technology. The vacancy generated by Ti combined C in high-entropy alloys can reduce the sintering temperature, promote sintering, and inhibit the growth of SiC grains through liquid phase sintering and improve the structure.
The preparation of high-performance SiC hard composite materials at lower sintering temperatures is achieved, which improves its hardness, fracture toughness and wear resistance, and expands its application areas.
Smart Images

Figure CN119800192A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a SiC hard composite material combined with a high entropy alloy and a preparation method thereof. Background Art
[0002] SiC composites are expected to become a substitute for WC-based cemented carbide because of their excellent hardness and low density. However, the phase change of SiC is complex and difficult to sinter. It can only be densified at 2500 ℃. SiC has low toughness and high brittleness. The toughness of pure SiC is about 3 MPa·m1 / 2. These two shortcomings greatly limit the application of SiC composites. It is urgent to find a suitable sintering aid to reduce the sintering temperature and improve the toughness of the material. Because SiC has a large bond energy and a strong directional covalent bond, the self-diffusion coefficient is quite low when sintered without other sintering aids, so sintering is difficult. At a high temperature of 2100 ℃, the diffusion coefficients of C atoms and Si atoms in SiC blocks are only 1.510-10 cm2 / s and 2.510-13 cm2 / s. At present, SiC composites can only be sintered by adding sintering aids or increasing the sintering temperature and pressure. However, too high a sintering temperature will cause SiC to sublimate and recrystallize, and the grains will grow again during the sintering process, greatly reducing the performance of the material. Sintering aids with low melting points will damage the material's antioxidant and high temperature resistance properties. In addition, the inherent brittleness of SiC also reduces the application areas of SiC composites. How to reduce the sintering temperature and toughen SiC composites is a hot topic in SiC composite research. Summary of the invention
[0003] The main purpose of the present invention is to provide a high-entropy alloy-bonded SiC hard composite material and a preparation method thereof. The high-entropy alloys of AlMnCuFeTi and AlZnCuFeTi prepared by mechanical alloying (MA) are used to prepare a metal-bonded phase silicon carbide hard composite material by spark plasma sintering (SPS). The vacancy energy generated by the combination of Ti and C in the high-entropy alloy can be used to reduce the sintering temperature and promote sintering, so that TiCx is formed in SiC, and the growth of SiC grains is inhibited and the organizational structure is improved by liquid phase sintering, thereby improving its hardness, fracture toughness, wear resistance and other properties.
[0004] In order to solve the above technical problems, the present invention discloses a SiC hard composite material combined with a high entropy alloy. The SiC hard composite material comprises the following components by mass percentage: 5-20wt.% of the high entropy alloy and the remainder of SiC.
[0005] According to one embodiment of the present invention, the particle size of the high entropy alloy is less than 150 nm; the purity of SiC is greater than 99%, and the particle size is less than 150 nm.
[0006] According to one embodiment of the present invention, the method for preparing the above-mentioned high entropy alloy-combined SiC hard composite material comprises the following steps: S1. Preparation of high entropy alloy powder: Mainly use AlMnCuFeTi or AlZnCuFeTi high entropy alloy. In a glove box filled with argon, mix the metal powders in a molar ratio of 1:1:1:1:1 and load them into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:1. The rotation speed is 300-600 r / min. The ball milling time is 20-50 h. The machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h. Then continue ball milling to obtain CoCrNiCuFe powder with a particle size of less than 150 nm. S2. Preparation of SiC powder: The SiC powder was ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain SiC powder with a particle size of 150 nm or finer. S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the SiC powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40-50 MPa, the sintering temperature is 1800-1900 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a silicon carbide composite material combined with a high entropy alloy.
[0007] According to one embodiment of the present invention, the purity of the high entropy alloy powder is >99%, wherein the particle size of the Co powder is 1-3 μm, the particle size of the Ni powder is 3-5 μm, and the particle size of the remaining metal element powders is <30 μm.
[0008] According to one embodiment of the present invention, the particle size of the SiC powder is 1-3 μm, and the purity is >99%.
[0009] According to one embodiment of the present invention, the ball milling processes in the above steps S1, S2 and S3 all use three types of large, medium and small SiC composite balls with diameters of 8 mm, 5 mm and 2 mm respectively, wherein the mass ratio of the large, medium and small SiC composite balls is 3:1:1.
[0010] According to one embodiment of the present invention, the specific sintering process in the above step S4 is: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate the sample to below 200 Pa; then, heat from room temperature to 600°C for 5 min, and keep it at 600°C for 10 min; then, heat from 600°C to 1800-1900°C at a heating rate of 50-100°C / min, and keep it for 3-30 min; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a silicon carbide composite material combined with a high entropy alloy.
[0011] Compared with the prior art, the present application can obtain the following technical effects: 1) The present invention uses high entropy alloys and high entropy ceramics as binders and sintering aids for SiC composites, and sintering is performed through a spark plasma sintering system to obtain composite materials with excellent performance. The strengthening and toughening mechanism between the high entropy binder and SiC is determined through different analytical test characterization methods. Suggestions are provided for the strengthening and toughening mechanism of high entropy binders and SiC composites and other composite material systems.
[0012] Of course, any product implementing the present invention does not necessarily need to achieve all of the above technical effects at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings: Figure 1 This is the SEM morphology of 10wt.% AlZnCuFeTi-SiC sintered at 1800 ℃.
[0014] Figure 2 This is the element distribution diagram of 10wt.% AlZnCuFeTi-SiC after sintering at 1800 ℃.
[0015] Figure 3 These are the XRD patterns of sintered bodies and unsintered powders of 10wt.% AlMnCuFeTi-SiC at different sintering temperatures.
[0016] Figure 4 XRD patterns of composite materials with different high entropy alloy contents sintered at 1900 ℃.
[0017] Figure 5 XRD patterns of 10wt.% AlZnCuFeTi-SiC composites sintered at different temperatures.
[0018] Figure 6 XRD patterns of AlZnCuFeTi-SiC composites with different contents sintered at 1800 ℃. DETAILED DESCRIPTION
[0019] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] It should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit exemplary embodiments according to the present invention. In addition, it should also be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates that there are features, steps, operations, devices, components and / or combinations thereof. Unless otherwise specifically stated, the relative arrangement of the parts and steps described in these embodiments, numerical expressions and numerical values do not limit the scope of the present invention. The technology, methods and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but in appropriate cases, the technology, methods and equipment should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following figures, so once a certain item is defined in one figure, it does not need to be further discussed in the subsequent figures.
[0021] The detection equipment described in the present invention are all instruments used in conventional detection means, such as X-ray diffractometer, Vickers hardness tester, apparent porosity density tester, scanning electron microscope, synchronous thermal analyzer, Gleeble thermal simulation tester, assembled material surface and interface performance tester, etc.
[0022] Exemplary embodiments, features and performance aspects of the present invention will be described in detail below.
[0023] Please refer to the above figure, Figure 1 This is the SEM morphology of 10wt.% AlZnCuFeTi-SiC sintered at 1800℃; Figure 2 This is the element distribution diagram of 10wt.% AlZnCuFeTi-SiC after sintering at 1800℃; Figure 3 XRD diagrams of sintered bodies and unsintered powders of 10wt.% AlMnCuFeTi-SiC at different sintering temperatures; Figure 4 XRD diagram of composite materials with different high entropy alloy contents sintered at 1900 ℃; Figure 5 XRD patterns of 10wt.% AlZnCuFeTi-SiC composites sintered at different temperatures; Figure 6 XRD patterns of AlZnCuFeTi-SiC composites with different contents sintered at 1800 ℃.
[0024] A high entropy alloy combined SiC hard composite material, the SiC hard composite material comprises the following components by mass percentage: 5-20wt.% of high entropy alloy, the remainder of SiC, the particle size of the high entropy alloy being less than 150 nm; the purity of SiC being greater than 99%, and the particle size being less than 150 nm.
[0025] A method for preparing a high entropy alloy-bonded SiC hard composite material comprises the following steps: S1. Preparation of high entropy alloy powder: Mainly use AlMnCuFeTi or AlZnCuFeTi high entropy alloy. In a glove box filled with argon, mix the metal powders in a molar ratio of 1:1:1:1:1 and load them into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:1. The rotation speed is 300-600 r / min. The ball milling time is 20-50 h. The machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h. Then continue ball milling to obtain CoCrNiCuFe powder with a particle size of less than 150 nm. S2. Preparation of SiC powder: The SiC powder was ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain SiC powder with a particle size of 150 nm or finer. S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the SiC powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40-50 MPa, the sintering temperature is 1800-1900 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a silicon carbide composite material combined with a high entropy alloy.
[0026] Furthermore, the purity of the high entropy alloy powder is greater than 99%, wherein the particle size of the Co powder is 1 to 3 μm, the particle size of the Ni powder is 3 to 5 μm, and the particle size of the remaining metal element powders is less than 30 μm.
[0027] Furthermore, the particle size of the SiC powder is 1 to 3 μm, and the purity is >99%.
[0028] Furthermore, the ball milling processes of steps S1, S2 and S3 all use three types of large, medium and small SiC composite balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small SiC composite balls is 3:1:1.
[0029] Furthermore, the specific sintering process in step S4 is: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate the sample to below 200 Pa; then, heat from room temperature to 600 °C in 5 min, and keep it at 600 °C for 10 min; then, increase the temperature from 600 °C to 1800-1900 °C at a heating rate of 50-100 °C / min, and keep it for 3-30 min; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a silicon carbide composite material combined with a high entropy alloy.
[0030] Table 1 Raw material specifications and ratios for preparing AlMnCuFeTi
[0031] Therefore, 10 groups of examples with different ratios were carried out according to the above method. Example 1
[0032] The raw material formula is weighed according to the following percentages: Table 2 Raw material formula for preparing 1.5 g silicon carbide composite material
[0033] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0034] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.35 g of SiC and 1.35 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0035] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 91.14%, the hardness reached 18.043 GPa, and the toughness reached 6.5 MPa·m 1 / 2 . Example 2
[0036] The raw material formula is weighed according to the following percentages: Table 3 Raw material formula for preparing 1.5 g silicon carbide composite material
[0037] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0038] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.35 g of SiC and 0.15 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0039] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 97.48%, the hardness reached 19.371 GPa, and the toughness reached 6.1 MPa·m 1 / 2 . Example 3
[0040] The raw material formula is weighed according to the following percentages: Table 4 Raw material formula for preparing 1.5 g silicon carbide composite material
[0041] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0042] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.275 g of SiC and 0.225 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating rate from room temperature to 571 °C at 110 °C / min, heating rate from 571 °C to 600 °C at 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1500 °C at 100 °C / min, heating at 50 °C / min for 6 min, heating at 25 °C / min for 4 min to 1900 °C, keeping at sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0043] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 97.38%, the hardness reached 18.511 GPa, and the toughness reached 5.28 MPa·m 1 / 2 . Example 4
[0044] The raw material formula is weighed according to the following percentages: Table 5 Raw material formula for preparing 1.5 g silicon carbide composite material
[0045] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0046] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.2 g of SiC and 0.3 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0047] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 95.14%, the hardness reached 15.974 GPa, and the toughness reached 5.34 MPa·m 1 / 2 . Example 5
[0048] The raw material formula is weighed according to the following percentages: Table 6 Raw material formula for preparing 1.5 g silicon carbide composite material
[0049] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0050] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.425 g of SiC and 0.075 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating rate from room temperature to 571 °C at 110 °C / min, heating rate from 571 °C to 600 °C at 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1500 °C at 100 °C / min, heating at 50 °C / min for 6 min, heating at 25 °C / min for 4 min to 1900 °C, keeping at sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0051] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 98.73%, the hardness reached 23.3414 GPa, and the toughness reached 5.94 MPa·m 1 / 2 . Example 6
[0052] The raw material formula is weighed according to the following percentages: Table 7 Raw material formula for preparing 1.5 g silicon carbide composite material
[0053] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0054] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.275 g of SiC and 0.225 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0055] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 94.61%, the hardness reached 21.3432 GPa, and the toughness reached 6.04 MPa·m 1 / 2 . Example 7
[0056] The raw material formula is weighed according to the following percentages: Table 8 Raw material formula for preparing 1.5 g silicon carbide composite material
[0057] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0058] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.425 g of SiC and 0.075 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0059] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 87.61%, the hardness reached 22.2198 GPa, and the toughness reached 5.68 MPa·m 1 / 2 . Example 8
[0060] The raw material formula is weighed according to the following percentages: Table 9 Raw material formula for preparing 1.5 g silicon carbide composite material
[0061] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0062] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.35 g of SiC and 0.15 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0063] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 95.84%, the hardness reached 23.032 GPa, and the toughness reached 5.52 MPa·m 1 / 2 . Example 9
[0064] The raw material formula is weighed according to the following percentages: Table 10 Raw material formula for preparing 1.5 g silicon carbide composite material
[0065] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0066] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.2 g of SiC and 0.3 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating from room temperature to 571 °C at a heating rate of 110 °C / min, heating from 571 °C to 600 °C at a heating rate of 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1400 °C at 100 °C / min, continuing to heat at 50 °C / min for 6 min, continuing to heat at 25 °C / min for 4 min to 1800 °C, keeping at the sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0067] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 94.84%, the hardness reached 20.76 GPa, and the toughness reached 5.66 MPa·m 1 / 2 . Example 10
[0068] The raw material formula is weighed according to the following percentages: Table 11 Raw material formula for preparing 1.5 g silicon carbide composite material
[0069] S1. Use stainless steel balls with diameters of 10 mm, 8 mm, and 6 mm, respectively. The mass ratio of large, medium, and small balls is 6:3:1. The mass of stainless steel balls in a single tank is 100 g, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh each raw material of the high entropy alloy according to equimolarity, a total of 10 g, put it into a stainless steel ball mill (GCr15 bearing steel, volume 125 mL), and add 0.2 mL of anhydrous ethanol as a dispersant. After the ball mill is sealed, place it on a high-energy ball mill (GN-2, China) for ball milling. Set the working voltage of the ball mill to 65 V (corresponding to a speed of 400 r / min), the ball milling time is 30 h, stop for 2 h for heat dissipation every 5 h, stop every 10 h to scrape off the raw materials stuck to the grinding balls and the inner wall of the tank and mix them, and then continue to add 0.2 mL of anhydrous ethanol to each tank for ball milling.
[0070] S2. Prepare SiC-HEA composite powder by ball milling. Use stainless steel balls with diameters of 10 mm, 8 mm and 6 mm respectively. The mass ratio of large, medium and small balls is 6:3:1. Put 100 g of steel balls into a single can, and the mass ratio of balls to materials is 10:1. In a glove box filled with argon, weigh 1.35 g of SiC and 0.15 g of high entropy alloy powder, put them in a steel can, seal the ball mill can, and place it on a high-energy ball mill (GN-2 model) for ball milling. Set the ball mill speed to 350 r / min and the ball milling time to 10 h. ; S3, pressure 40 MPa, argon atmosphere, heating rate from room temperature to 571 °C at 110 °C / min, heating rate from 571 °C to 600 °C at 30 °C / min, keeping at 600 °C for 5 min, heating from 600 °C to 1500 °C at 100 °C / min, heating at 50 °C / min for 6 min, heating at 25 °C / min for 4 min to 1900 °C, keeping at sintering temperature for 10 min. Cooling with the furnace to obtain a blank. The prepared blank was subjected to surface grinding and deburring treatment to obtain a silicon carbide hard composite material.
[0071] The hot-pressed sintered tungsten carbide cemented carbide composite material samples were polished and then tested for microstructure and performance. The density of the sintered block reached 95.35%, the hardness reached 21.263 GPa, and the toughness reached 5.16 MPa·m 1 / 2 .
[0072] Experimental data summary: It can be seen from Examples 1-10 that the sintering temperature, high entropy alloy type and content have a greater impact on the performance of SiC cemented carbide. It can be seen from Examples 1-6 that with the increase of AlMnCuFeTi content, the performance of the composite material can be improved. AlZnCuFeTi also has a similar function. Both can improve the performance of the composite material through liquid phase sintering combined with the diffusion of C vacancies. The SiC hard material with the addition of high entropy alloy has a smaller grain size and the best hardness, toughness and wear resistance.
[0073] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A high entropy alloy combined SiC hard composite material, characterized in that: The composite material comprises the following components in terms of mass percentage: high entropy alloy accounts for 5-20wt.%, and the remainder is SiC.
2. The high entropy alloy-bonded SiC hard composite material according to claim 1, characterized in that: The particle size of the high entropy alloy is less than 150 nm; the purity of SiC is greater than 99%, and the particle size is less than 150 nm.
3. A method for preparing a SiC hard composite material combined with a high entropy alloy as claimed in claim 1 or 2, characterized in that The following steps are included: S1. Preparation of high entropy alloy powder: Mainly use AlMnCuFeTi or AlZnCuFeTi high entropy alloy. In a glove box filled with argon, mix the metal powders in a molar ratio of 1:1:1:1:1 and load them into a WC composite material ball mill. The ball-to-material mass ratio is 10:1-20:
1. The rotation speed is 300-600 r / min. The ball milling time is 20-50 h. The machine is stopped for 30 min every 5 h to dissipate heat. The raw materials adhering to the grinding balls and the inner wall of the tank are scraped off and mixed after stopping every 10 h to obtain CoCrNiCuFe powder with a particle size of less than 150 nm. S2. Preparation of SiC powder: The SiC powder was ball-milled, with a ball-to-material mass ratio of 10:1 to 20:1, a rotation speed of 250 to 400 r / min, a ball-milling time of 10 to 40 h, and a 30-min stop for heat dissipation every 5 h to obtain SiC powder with a particle size of 150 nm or finer. S3, mixing: in a glove box filled with argon, weigh 5-30wt.% of the high entropy alloy powder prepared in step S1, add it to the SiC powder prepared in step S2, and then ball mill the mixture, the ball:material mass ratio is 5:1-10:1, the rotation speed is 200-350 r / min, the ball milling time is 2-5 h, and the mill is stopped for 10 min every 1 h for heat dissipation; S4, sintering preparation: the mixed material obtained in step S3 is loaded into a graphite mold for pre-compression, the pre-compression pressure is 10-30 MPa, and the pre-compression is 60 s; then spark plasma sintering is performed, the vacuum degree is 40 Pa, the sintering pressure is 40-50 MPa, the sintering temperature is 1800-1900 ℃, the heating rate is 50-100 ℃ / min, and the holding time is 5-15 min; then the temperature is reduced and the pressure is released to obtain a silicon carbide composite material combined with a high entropy alloy.
4. The method for preparing the high entropy alloy-bonded SiC hard composite material according to claim 3, characterized in that: The purity of the high entropy alloy powder is greater than 99%, wherein the particle size of the Co powder is 1 to 3 μm, the particle size of the Ni powder is 3 to 5 μm, and the particle size of the remaining metal element powders is less than 30 μm.
5. The method for preparing the high entropy alloy-bonded SiC hard composite material according to claim 3, characterized in that: The SiC powder has a particle size of 1 to 3 μm and a purity of more than 99%.
6. The method for preparing the high entropy alloy-bonded SiC hard composite material according to claim 3, characterized in that: The ball milling processes of steps S1, S2 and S3 all use three types of large, medium and small SiC composite balls with diameters of 8 mm, 5 mm and 2 mm, respectively, wherein the mass ratio of the large, medium and small SiC composite balls is 3:1:
1.
7. The method for preparing the high entropy alloy-bonded SiC hard composite material according to claim 3, characterized in that: The specific sintering process in step S4 is as follows: first, slowly apply pressure to the sample to 40-50 MPa; then, evacuate the sample to below 200 Pa; then, heat from room temperature to 600 °C in 5 min, and keep it at 600 °C for 10 min; then, heat from 600 °C to 1800-1900 °C at a heating rate of 50-100 °C / min, and keep it at that temperature for 3-30 min; cool with the furnace to obtain a blank; perform surface grinding and deburring on the prepared blank to obtain a silicon carbide composite material combined with a high entropy alloy.
Citation Information
Cited By
Silicon carbide ceramic gas filtering membrane with catalytic function and preparation method thereof
CN121372051A
Nano high-entropy alloy toughened silicon carbide ceramic filter membrane and preparation method thereof
CN121372066A
Nano high-entropy alloy reinforced silicon carbide ceramic filter membrane and preparation method thereof
CN121372067A
High-strength high-entropy alloy for inducing sigma / VC / M7C3 multiphase precipitation through nano SiC and preparation method
CN121472683A
A high-strength, high-entropy alloy induced by nano-SiC precipitation of σ / VC / M7C3 multiphase and its preparation method
CN121472683B